HOW DOES SOCIAL MEDIA MARKETING INFLUENCES YOUTH CUSTOMERS? A LITERATURE REVIEW - Nur Rafiqah binti Tahir; Milfadzhilah Mohd Jamil; Mariatul Qibtiyah binti Hasloni; Khairun Nisa binti Jumali; Jahlelawati binti Yub Rembeli; Nuramera binti Amir (International Journal of Accounting, Finance and Business, 2022)
The influence of social media is enormous and is the most powerful medium,especially in the field of marketing in the current era of modernization. Numerous methods ofsocial media advertising and marketing can attract consumers of various ages, especiallyyouth. This paper aims at presenting the reviews of the literature on social media influencingthe youth consumer. The previous studies give positive feedback on social media as one of themarketing tools to influence the customer and consumer, especially youth. The review will givea holistic understanding of the social media influencing youth and marketing concepts forfuture researchers and aid to identify the research gap.